2022
DOI: 10.48550/arxiv.2202.03628
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Graph-Relational Domain Adaptation

Abstract: Existing domain adaptation methods tend to treat every domain equally and align them all perfectly. Such uniform alignment ignores topological structures among different domains; therefore it may be beneficial for nearby domains, but not necessarily for distant domains. In this work, we relax such uniform alignment by using a domain graph to encode domain adjacency, e.g., a graph of states in the US with each state as a domain and each edge indicating adjacency, thereby allowing domains to align flexibly based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Dual-stream architectures [59][60][61][62][63][64][65][66][67][68][69][70][71][72] and approaches that operate directly on image features [73][74][75] are representative ways to perform discrepancy-based DTL. In addition, optimizing the network architecture [99] and improving the feature alignment [100][101][102][103] have also received attention from researchers in recent years. The essence of the above approaches is to minimize the feature differences between the source and target domain datasets.…”
Section: Discrepancy-based Dtlmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual-stream architectures [59][60][61][62][63][64][65][66][67][68][69][70][71][72] and approaches that operate directly on image features [73][74][75] are representative ways to perform discrepancy-based DTL. In addition, optimizing the network architecture [99] and improving the feature alignment [100][101][102][103] have also received attention from researchers in recent years. The essence of the above approaches is to minimize the feature differences between the source and target domain datasets.…”
Section: Discrepancy-based Dtlmentioning
confidence: 99%
“…L2M is a versatile framework that has shown excellent performance in the application of transfer of pneumonia to COVID-19 chest X-ray images. [100] proposed to use topology to accomplish domain adaptation. This approach reduces the effect of uniform alignment by using domain maps to encode neighboring domains.…”
Section: Operation With Image Featuresmentioning
confidence: 99%
“…These DA methods for fault diagnosis have shown their feasibility in dealing with varying operating conditions. However, existing DA methods tend to treat all domains equally and align them all perfectly [ 12 ]. Several works [ 13 , 14 , 15 ] attempted to demonstrate that the domain weighting schemes used on different source domains could enhance the generalizing ability to the target domain and ensemble models can handle the weights dynamically for the target [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the setting values of operating parameters are typically managed and stored as metadata with the datasets. Although recent studies [ 12 , 18 ] have shown that leveraging the metadata could improve the domain adaptation, this approach remains relatively unexplored in the field of fault diagnosis.…”
Section: Introductionmentioning
confidence: 99%